2015
DOI: 10.1103/physrevb.92.024104
|View full text |Cite
|
Sign up to set email alerts
|

Charge localization in the Verwey structure of magnetite

Abstract: The thermal evolution of electronic order in the complex Verwey ground state of magnetite (Fe 3 O 4 ) has been determined through 22 high-accuracy synchrotron x-ray structure refinements using three 10-40 μm grains of stoichiometric magnetite. A robust fitting function is introduced to extract values of order parameterlike quantities at zero temperature and at the upper limit of the Verwey phase T u = 123.4 K. The low-temperature structural distortion is found to be almost frozen below the Verwey transition bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 27 publications
(36 reference statements)
4
41
0
Order By: Relevance
“…The main reason may be from the distorted lattice and charge transfer. The distortion at the Fe 3 O 4 lattice mainly come from the interface effect rather than orbital ordering, which is different from the bulk and surface phase . Different Fe B sites are created by the effect and different symmetry point group ( Pmm 2), which make the orbital splitting different from the bulk phase, and influence the transition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason may be from the distorted lattice and charge transfer. The distortion at the Fe 3 O 4 lattice mainly come from the interface effect rather than orbital ordering, which is different from the bulk and surface phase . Different Fe B sites are created by the effect and different symmetry point group ( Pmm 2), which make the orbital splitting different from the bulk phase, and influence the transition.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, trimeron units composed of two Fe 3+ and one Fe 2+ were reported by Wright et al, who characterized the low‐temperature structure of Fe 3 O 4 using a high‐energy X‐ray method and found that many frozen lattice modes contribute to the Cc superstructure. In their studies, they analyzed the main reason for the phenomenon and deduced that the t 2g electron of the Fe 2+ is delocalized, which causes a decrease in the length of Fe–Fe due to the lowering of Coulomb repulsion, and found the electron localization within trimerons is the driving force behind the phase transition . Above T = 221 K, the short‐range correlations still remain …”
Section: Introductionmentioning
confidence: 99%
“…In the structural transition of magnetite, complex atomic displacements, with small amplitudes down to 1 pm, give rise to a change in crystal symmetry, which is reflected in the modifications of a number of physical properties [2][3][4][5]. A monoclinic cell four times larger than the cubic cell accounts for the complete set of structural distortions that take place upon decreasing the temperature from above to below T V .…”
Section: A Phonon Excitationsmentioning
confidence: 99%
“…On cooling across the transition temperature, also referred to as the Verwey temperature, T V , the former is lowered from cubic to monoclinic, whereas the latter changes from conductive to insulating. In the past two decades, accurate diffraction experiments disclosed the most elusive features of the crystal structure and the charge and orbital order in the monoclinic phase [2][3][4][5]. In particular, the constitutive units of the sublattice of octahedral Fe ions, or B-type Fe ions, are small polarons (SPs) named trimerons, comprised of an extra electron delocalized over three ions and the atomic displacements of the end ions toward the central ion [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation